PTU-039 Outcome of endoscopic mucosal resection of 424 large sessile colonic polyps (≥20 mm) over a 9 year period: a single centre experience and analysis of change with time. (22nd June 2015) - Lim, DNF; Moore, A; DeCaestecker, J; Robinson, R; Wurm, P
Abstract : Introduction: Endoscopic mucosal resection (EMR) is now standard for resection of large sessile colonic polyps. We aimed to assess the clinical outcome of colonic EMR of polyps ≥2 cm size at a University Hospital and changes over a 9 year period. Method: Data was collected for all sessile colonic polyps ≥20 mm removed by EMR between 2006 and 2014 by 3 endoscopists. Patient demographics, resection technique, completeness of initial resection, recurrence rate at first surveillance (SC1), polyp eradication at 2 nd surveillance after at least 1 year (SC2) and complication rates were analysed. Results: 564 patients were assessed for EMR, 424 completed EMRs (BCSP138, Symptomatic286). Of the 140 not having complete EMR, 65 with no attempt at EMR were referred for surgery (cancer 31, technical difficulty 34).32 EMR was attempted but abandoned; all were referred for surgery (cancer 18, benign polyp 14). Finally, 43 had no intervention (13 declined, 22 non-adenomatous polyps, 8 moved away). Mean age 68.7 years (range 25–93), male 226 (53%), female 198 (47%). Mean polyp size 33 mm (median 30 mm). Polyp site right colon 27%, transverse 5%, left 68% (rectum 58%, sigmoid 4%, descending 6%). Piecemeal EMR 381 (90%), 'en bloc'43 (10%). Those who have undergone surveillance, recurrence was found in 56/284 (19.7%) at initial SC1 (mean 7 month; range 2–36) and was endoscopically treated in 53/56 (94.6%); 3/56 (5.4%) referred for surgical resection (2 cancer, 1 non lifting). Complete eradication after one year SC2 (mean 16 months; range 5–51) 211/234 (90.2%) with recurrence in 23 (9.8%)–22/23 endoscopically resected. Overall complication rate 17/424 (4%):caecal perforation 1/424 (0.2%) and post polypectomy pain syndrome 14 (3.3%) all treated conservatively; delayed bleeding 2 (0.5%) required endoscopic therapy to achieve haemostasis. No deaths. For each 3 year period (2006–8, 2009–11, 2012–14), there was reduction in number of polyps not treated endoscopically or requiring surgery (overall decrease of 15.7%), incomplete EMR referred for surgical resection (overall decrease of 2.3%) and recurrence at first SC1(overall decrease 16.3%). There were increases in numbers of EMRs performed (overall increase 26%), mean polyp size resected (+7 mm), level 3 and 4 polypectomies (3.7 and 7%) and complete eradication rate at SC1 (16.3%). Conclusion: This EMR series of 424 sessile colonic polyps >2 cm was performed by 3 operators over a 9 year period; 19.7% had recurrence at initial surveillance, most managed endoscopically, with eradication rate at 1 year of over 90% (22/23 one year recurrences treated endoscopically). Time trends showed progressive reduction in recurrence and a trend for larger, more complex polyps to be resected endoscopically, with a corresponding drop in surgical management, demonstrating improvement in outcome with time. Disclosure of interest: None Declared.